The interaction effects of pri-let-7a-1 rs10739971 with PGC and ERCC6 gene polymorphisms in gastric cancer and atrophic gastritis. - Qian Xu; Jing-wei Liu; Cai-yun He; Li-ping Sun; Yue-hua Gong; Jing-Jing Jing; Cheng-zhong Xing; Yuan Yuan (PLoS ONE)
Background The aim of this study was to investigate the interaction effects of pri-let-7a-1 rs10739971 with pepsinogen C (PGC) and excision repair cross complementing group 6 (ERCC6) gene polymorphisms and its association with the risks of gastric cancer and atrophic gastritis. We hoped to identify miRNA polymorphism or a combination of several polymorphisms that could serve as biomarkers for predicting the risk of gastric cancer and its precancerous diseases. Methods Sequenom MassARRAY platform method was used to detect polymorphisms of pri-let-7a-1 rs10739971 G → A, PGC rs4711690 C → G, PGC rs6458238 G → A, PGC rs9471643 G → C, and ERCC6 rs1917799 in 471 gastric cancer patients, 645 atrophic gastritis patients and 717 controls. Results An interaction effect of pri-let-7a-1 rs10739971 polymorphism with ERCC6 rs1917799 polymorphism was observed for the risk of gastric cancer (P interaction = 0.026); and interaction effects of pri-let-7a-1 rs10739971 polymorphism with PGC rs6458238 polymorphism (P interaction = 0.012) and PGC rs9471643 polymorphism (P interaction = 0.039) were observed for the risk of atrophic gastritis. Conclusion The combination of pri-let-7a-1 rs10739971 polymorphism and ERCC6 and PGC polymorphisms could provide a greater prediction potential than a single polymorphism on its own. Large-scale studies and molecular mechanism research are needed to confirm our findings.